PEMBENTUKAN AKHLAKUL KARIMAH ANAK USIA DINI MELALUI PANDUAN ORANGTUA DAN GURU DI SEKOLAH - Bahtiar Siregar (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
Planting Akhlakul Karimah In early childhood is an effort done by parents teachers cooperate harmoniously. This is particularly relevant to the current situation where many early childhood children are not getting an education from a busy parent with a career. Thus the method offered rests on 2 forms of activities namely: 1). Day activities through transparency, advice, motivation, gift giving, habituation penalties and supervision. 2) The obesity is programmatic through learning and habituation in school. Thus, the process of forming Akhlakul Karimah in students will be achieved as expected by parents and teachers.